Limb/trunk lean mass ratio as a risk factor for mortality in peritoneal dialysis patients - Seok Hui Kang; Kyu Hyang Cho; Jong Won Park; Kyung Woo Yoon; Jun Young Do (The Korean Society of Nephrology, 2012)
Protein energy wasting (PEW) is a common problem in dialysis patients. There have been few reports on the effects of regional lean mass distribution for peritoneal dialysis (PD) patients. We reviewed the medical records and identified all adults who received PD between May 2001 and May 2011. Five hundred thirty four patients were enrolled. The clinical and laboratory data were collected at 1 and 12 months. Regional lean masses were measured by dual-energy X-ray absorptiometry. The limb/trunk lean mass ratio (LTLM) was defined as a value on dividing the sum of four limbs by the trunk lean mass. The mean age at the start of PD was 53.2±14.1 years. Diabetes mellitus (DM) was most common underlying disease of end-stage renal disease (49.6%). In males, the low LTLM tertile was associated with low body mass index, creatinine, arm muscle circumference, and high C-reactive protein. In females, the low LTLM tertile was associated with low creatinine and normalized protein equivalent of nitrogen appearance. On both univariate and multivariate analysis adjusted for age, Davies risk index, and residual renal function, initial low LTLM tertile and maintenance of low LTLM were associated with mortality in PD patients. Distribution or change of regional lean mass may be more useful for predicting nutritional status. Initial low LTLM and maintenance of low LTLM were associated with mortality in PD patients. LTLM as a new marker would be useful for predicting the nutritional status and the mortality in patients on PD.